Analyzing Factors Influencing Milk Marketing Channel Strategies in Punjab (Indian Journal of Extension Education, 2024)
Raising livestock has long been regarded as an important activity in the nation’s rural areas. The Indian dairy industry has undergone noteworthy changes with the tremendous increase in the production of milk. The provision of assured marketing channels is crucial for dairy farmers to reap the economic benefits of milk production. The present study aims to examine the drivers behind the dairy farmers’ decisions about milk marketing channels in Punjab. The primary data used in this study has been collected from 21 villages and 420 dairy farmers using a multistage sampling technique in 2019, belonging to three different zones of the state. Henry Garrett’s Ranking Technique was used to determine the significant factors influencing their choice of milk marketing channels. Higher milk price, with a mean value of 71.64, is found to be the main driver for choosing the milk marketing channel, followed by doorstep collection with a mean value of 56.70, and provision of advances with a mean value of 54.55. There is a need to strengthen the dairy cooperatives to reduce the involvement of the unorganized sector in the marketing of milk in the state of Punjab.